DETERMINATION OF TOXIC HEAVY METALS IN CHOLIC ACID USING QUADRUPOLE INDUCTIVELY COUPLED PLASMA MASS SPECTROMETRY - Kumar, Thakar Meet; Vaishali, Suthar; Jateen, Sheth; Pulidindi, Indra Neel; PANKAJ, SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The information on the presence of toxic heavy metals in pharmaceutical starting materials and finished product is very crucial from the viewpoint of human life and its hazardous impact on the worldwide environment. The present work deals with the detailed quantification of the toxic heavy metals, namely, V, Co, Ni, Cd, Hg, Pb, and As, present in colic acid using quadrupole inductively coupled plasma mass spectrometry (Q-ICPMS) with prior microwave-assisted digestion. Moreover, the preliminary characterization of commercially available cholic acid by FT-IR, NMR (1H and 13C), SEM-EDAX has also been carried out. Methods: Cholic acid of synthesis grade, Nitric acid (65%) AR. grade, ethylene diamine tetra acetic acid sodium salt AR grade, and certified reference metal stock standard solutions (1000 mg/L) of multiple elements prepared in 2–3% HNO3 of analytical grade were purchased from Merck (Darmstadt, Germany). All the samples were treated with nitric acid and microwave-assisted digestion. For the accurate determination of the elemental amount, various digested solutions and post-digestion diluents were tested. The linearity, accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ) of the analytical technique were evaluated in accordance with the United States Pharmacopoeia 233 standard. Results and Discussion: The Q-ICPMS-based analytical method was validated for specificity, LOD, LOQ, linearity, accuracy, precision, and uncertainty. The estimated detection limits of the toxic heavy metals in cholic acid were in the range 2–180 μg/L. The quantification limits were in the range of 1.5–60 μg/L. Mean recoveries±standard deviations at different spiking levels were in the range 75.3±2.1–104.9±8.5%. The coefficients of variation were in the range of 0.5–8.1%. Conclusion: The precision of the analytical method, in terms of relative standard deviation, was below 1.95%. The uncertainty in the quantification of all the validated elements was found to be ≤1.70% for Sample 1.